Selling through referrals. Issue 4 (11th May 2018) - Condorelli, Daniele; Galeotti, Andrea; Skreta, Vasiliki
Abstract: We endogenize intermediaries' choice to operate as agents or merchants in a market where there are frictions due to asymmetric information about consumption values. A seller has an object for sale and can reach buyers only through intermediaries. Intermediaries can either mediate the transaction by buying and reselling— the merchant mode —or refer buyers to the seller for a fee— the referral mode . When the seller has a strong bargaining position and can condition the asking price to the intermediaries' business model choice, all intermediaries specialize in agency. The seller's and intermediaries' joint profits equal the seller's profits when he has access to all buyers. When the seller does not have such bargaining power, the level of the referral fee and the degree of competition among intermediaries determine the business mode adoption. A hybrid agency–merchant mode may be adopted in equilibrium. Banning the referral mode can decrease welfare because the merchant mode is associated with additional allocative distortions due to asymmetric information.